Análise da influência da energia de superfície no comportamento tribológico de revestimentos (AlCrN e TiAlN) em deslizamento contra aço AISI 4340 - Poliana Santos Souza (2020)
The performance of metal cutting tools is drastically affected by the presence of hard coatings, which promote longer tool lives, higher productivity and superior quality to the machined components. Nevertheless, the conventional properties (such as hardness, fracture toughness, modulus of elasticity, etc.) used to select the most appropriate tool material for a given operation are not capable to fully predict the behavior of the tool during the operation, therefore, this work investigates the applicability of the surface energy as a property which can be associated with the performance of AlCrN and TiAlN coated materials. Surface energy (γ) of solids is a characteristic factor which affects the contact interactions in sliding, i.e. adsorption, wetting and adhesion. However, one of the reasons for γ to be often neglected in tribological studies and engineering design models is the lack of understanding about the correlation between them, mainly for typical engineering materials in friction without lubricant. In this study, AlCrN and TiAlN coatings were deposited on AISI M2 by physical vapor deposition (PVD) by magnetron sputtering process. Coatings were characterized in detail by thickness and topography (SEM); elemental composition (EDS); structure (XDR); hardness, modulus of elasticity and roughness (AFM); wettability and surface energy (goniometer); and adhesion to the substrate (Scratch test and Rockwell test). For the tribological evaluation were performed sliding tests of the type Pin-on-disk (tribometer) against AISI 4340 steel. The AlCrN coating showed a lower friction coefficient than the TiAlN coating under different sliding conditions (light and severe) and its sliding contact with AISI 4340 steel caused a lower wear rate. The wear analysis in the TiAlN vs. AISI 4340 pair showed a marked influence of adhesion in contact (transferred material). The evaluated properties and characteristics of the coatings did not show significant differences that would justify the tribological behavior. However, the comparison between surface energy interaction (Polar-Polar; Dispersive-Dispersive and Dispersive-Polar) and wear indicated that the larger proportion of Dispersive-Dispersive interaction may have favored adhesive wear. The surface energy can contribute to evaluating and selecting materials for tribological applications.